Reduced Cardiotoxicity of Ponatinib-Loaded PLGA-PEG-PLGA Nanoparticles in Zebrafish Xenograft Model - Al-Thani, Hissa F; Shurbaji, Samar; Zakaria, Zain Zaki; Hasan, Maram H; Gorachinova, Katerina; Korashy, Hesham M; Yalcin, Huseyin C (MDPI, 2022)
Tyrosine kinase inhibitors (TKIs) are the new generation of anti-cancer drugs with high potential against cancer cells' proliferation and growth. However, TKIs are associated with severe cardiotoxicity, limiting their clinical value. One TKI that has been developed recently but not explored much is Ponatinib. The use of nanoparticles (NPs) as a better therapeutic agent to deliver anti-cancer drugs and reduce their cardiotoxicity has been recently considered. In this study, with the aim to reduce Ponatinib cardiotoxicity, Poly(D,L-lactide-co-glycolide)-b-poly(ethyleneoxide)-b-poly(D,L-lactide-co-glycolide) (PLGA-PEG-PLGA) triblock copolymer was used to synthesize Ponatinib in loaded PLGA-PEG-PLGA NPs for chronic myeloid leukemia (CML) treatment. In addition to physicochemical NPs characterization (NPs shape, size, size distribution, surface charge, dissolution rate, drug content, and efficacy of encapsulation) the efficacy and safety of these drug-delivery systems were assessed in vivo using zebrafish. Zebrafish are a powerful animal model for investigating the cardiotoxicity associated with anti-cancer drugs such as TKIs, to determine the optimum concentration of smart NPs with the least side effects, and to generate a xenograft model of several cancer types. Therefore, the cardiotoxicity of unloaded and drug-loaded PLGA-PEG-PLGA NPs was studied using the zebrafish model by measuring the survival rate and cardiac function parameters, and therapeutic concentration for in vivo efficacy studies was optimized in an in vivo setting. Further, the efficacy of drug-loaded PLGA-PEG-PLGA NPs was tested on the zebrafish cancer xenograft model, in which human myelogenous leukemia cell line K562 was transplanted into zebrafish embryos. Our results demonstrated that the Ponatinib-loaded PLGA-PEG-PLGA NPs at a concentration of 0.001 mg/mL are non-toxic/non-cardio-toxic in the studied zebrafish xenograft model.
Keywords: PLGA; Ponatinib; cancer; cardiotoxicity; leukemia; nanomedicine; nanoparticle; pre-clinical; xenograft; zebrafish.